7 - Programmes «d'ajustement structurel» du FMI - Najib AKESBI, (Africa Development, 1985)
Morocco, like most African countries undergoing economic diffi culties, also resorted to IMF for solutions. In the first and second parts of his paper, AKESBI undertakes a description and a critical analysis of the theoretical bases of the IMF strategy as applied in every country that requested assistance from the IMF. In the tnird part, the Moroccan case is used as an illustration to his discussions. He then concludes his paper on a number of policies to adopt as an alternative to IMF dictates. On the theoretical bases of the IMF strategy, AKESBI points out that, from the Fund point of view, the economic problems of Third World countries are internally generated and the State is responsible first and foremost for its own difficulties. Hence the necessity of a liberal monetary strategy and the recommendations still in keeping with the neo-classical doctrines. The primary concern of IMF is in fact to try and restore everywhere the financial balance as if the latter was more important than others, namely, the economic balance and more so the social balance. AKESBI also feels that not only are priorities set in this manner, among the various equilibria, hardly objective but with reference to this very financial balance which is given precedence over the others, the failings in the IMF stabilization programmes are their very inefficiency ana inconsistency. This applies especially to budget deficits which are induced from the outset by a wrong diagnosis and which immediately cause an over-destruction of economies. It also applies to the large-scale devaluation programmes always following IMF recommendations which turn out to be inefficient and dangerous in view of their negative impact on the trade balance, on imports and on interna/ unbalances. It finally holds true for actual prices which are in fact set by «powers» and for privatization which has not come up to expectations in spite of all the allowances being made for over twenty five years. Back to the Moroccan case, AKESBI feels that there is nothing special in the experience of this country as far as applying IMF remedies is concerned. On the contrary such an experience is the epitome of the failure of the structural re-adjustment policy, based on the above mention ed causes. In concluding his paper, AKESBI makes three proposals which, he believes, are a pre-requisite for any real structural change. These are: To refuse to comply with IMF dictates and obtain at least a 5 - 10 year grace period for renmbursement of the external debt without any strings attached to the domestic economic and financial policy of countries concerned. To consolidate the role of the State as the driving force of economic development, which does not preclude the need to undertake a radical change in both the form and substance of State intervention and a reorganization of the public sector management. To reverse priorities as to the desired development objective i.e. to give priority to fulfilling basic needs over satisfying the whims of outside markets.